Butterfly species in Bogani Nani Wartabone National Park, North Sulawesi, Indonesia - Roni Koneri; Meis Jacinta Nangoy; Pience Veralyn Maabuat; Wakhid Wakhid (Society for Indonesian Biodiversity, 2023)
Abstract. Koneri R, Nangoy MJ, Maabuat PV, Wakhid. 2023. Butterfly species in Bogani Nani Wartabone National Park, North Sulawesi, Indonesia. Biodiversitas 24: 1242-1251. Changes in the landscape spatially and temporally impacted the fauna distribution and diversity, such as butterflies. This research analyzed the diversity in the Bogani Nani Wartabone National Park area, in Toraut Village, West Dumoga Sub-district, Bolaang Mongondow District, North Sulawesi, Indonesia. A survey method was used with purposive sampling in 4 habitats: a waterfall located within the national park area, forest edge, agricultural land, and shrubs. The sampling and sweeping techniques following the line transect were applied randomly along 300 m in each habitat type. Furthermore, data analysis included distribution, abundance, richness index, diversity index, species evenness index, the correlation between environmental factors and species diversity, and butterfly species similarity index between habitats. Overall, 1594 individuals from 71 species in 5 families were identified. The family with the highest number of species and individuals was Nymphalidae, while the most common was Catopsilia scylla of the orange emigrant. The highest average abundance and evenness were found at the forest edge, while the highest richness and diversity were in the waterfall. According to the analysis of similarity (ANOSIM), the composition of butterflies in four habitats was significantly different. Principal component analysis (PCA) showed that the waterfall habitat was characterized by high relative humidity, low air temperature, and light intensity. The ordinance plot represented a waterfall separated from the three other habitats; hence, the environmental factors differed. Waterfall and forest edges had the highest diversity due to the complex vegetation structure and environmental factors supporting survival.